FRI0493 Disease activity together with depression contributes to work disability in psoriatic arthritis. (15th June 2017) - Farkas, F; Ikumi, N; Szentpetery, A; Kirby, B; FitzGerald, O
Abstract : Background: Work disability (WD) is an important functional outcome measure in inflammatory arthritis, which has been studied comprehensively in rheumatoid arthritis and ankylosing spondylitis, however limited data are available in psoriatic arthritis (PsA) 1 . Depression and anxiety are well known comorbidities in psoriasis and PsA with higher prevalence in PsA 2 . Objectives: The aim of this study was to compare 1) patient-reported outcomes (PROs), including depression/anxiety scores; 2) physician-assessed measures and 3) disease activity using minimal disease activity (MDA) and Composite Psoriatic Disease Activity Index (CPDAI) in PsA patients with and without WD. Methods: Consecutive patients with PsA fulfilling the CASPAR criteria were enrolled. Patients on disability pension, those with early retirement due to arthritis, those unemployed, away from work due to sick leave were considered as having WD. Patients have completed questionnaires on physical function and health-related quality of life and they were assessed for depression/anxiety using the Hospital Anxiety and Depression Scale (HADS-A and HADS-D) and Penn State Worry Questionnaire (PSWQ). Patients underwent musculoskeletal and skin assessments. Disease activity was compared between work-disabled and employed patients using MDA and CPDAI. Mann-Whitney, Chi-square tests and linear regression model were used to perform statistical analysis. Results: 100 PsA patients were recruited, 18 were natural retirees, leaving 82 patients available for analysis. Thirty-one (17 male, age 50.9±9.97 years) participants of working age had work disability versus fifty-one (29 male, age 49.1±8.65 years) employed patients. Work-disabled patients had significantly higher HADS-D score (5.07±3.01 vs. 2.57±2.64; p<0.001) and significantly worse PROMs, including HAQ, PsAQoL, EQ-5D, BASDAI, BASFI, ASQoL, BRAF-NRS, pain and general health VAS. HADS-A and PSWQ scores were similar in both groups. Leeds enthesitis index and ESR were significantly higher (p=0.008; p=0.04, respectively) in patients with WD compared to those employed; furthermore the % of patients with CPDAI>4, suggesting moderate to severe disease activity were significantly higher (51.6% vs. 28%; p=0.032) in the WD group. There was no significant difference in MDA status between the two groups. Multiple regression analysis revealed significant relationship between HADS-D scores and CPDAI (B=0.566; p=0.03). Conclusions: Consistent with previous studies we have observed that the WD rate is high (37.8%) among patients with PsA. This is the first study assessing the relationship between depression and disease activity using CPDAI in PsA patients with work disability. We have found significantly higher HADS-D score and higher % of patients with CPDAI>4 in the WD group compared to those employed. Significant relationship was revealed between depression and CPDAI, which suggests that disease activity together with depression contributes to work disability in PsA. References: Tillett W. Rheumatology (Oxford) 2012. McDonough E. JRheumatol 2014. Disclosure of Interest: F. Farkas: None declared, N. Ikumi: None declared, A. Szentpetery: None declared, B. Kirby Grant/research support from: Abbvie, O. FitzGerald Grant/research support from: Abbvie, Pfizer, BMS, Consultant for: Abbvie, Pfizer, BMS, Celgene, Janssen, Novartis, UCB, Eli Lilly